SIMULASI KEBAKARAN RUMAH TANGGA DI WILAYAH DI WILAYAH SAMAAN SUDIROPRAJAN - Silvitasari, Ika; Didik Iman Margatot; Fida’Husain; Panggah Widodo (P3M Universitas Aisyiyah Surakarta, 2025)
The Surakarta City Fire Department recorded fire incidents that occurred in 2023 reaching 132 incidents in the city and 125 incidents outside the city. As a result, residential locations become denser and denser, thereby increasing the risk of fire. The impacts of fire include loss of life, physical damage to buildings, loss of property and economic loss and environmental damage. Increasing understanding and skills regarding fire management can reduce the impact caused by fire. The target and output is to increase community knowledge and skills regarding handling household fires in the Samaan Sudiroprajan area. The implementation method is by providing counseling and simulations in collaboration with the Surakarta City Fire Department, the community tries to extinguish fires, evaluates community skills. The results of this activity were the level of community knowledge before being given counseling. Most of the participants were in the sufficient category, namely 18 people (90%), and after being given counseling, the majority of participants were in the good category, namely 20 people (100%). Community skills were obtained after carrying out simulations on 15 (100%) people, all in the good category. The conclusion from this activity is that providing counseling and simulations can increase people's knowledge and skills in dealing with household fires.